Biomechanical Adaptations and Performance Indicators in Short Trail Running - Björklund, Glenn; Swarén, Mikael; Born, Dennis-Peter; Stöggl, Thomas (Frontiers in Physiology, 2019)
Our aims were to measure anthropometric and oxygen uptake (〖V ̇O〗_2) variables in the laboratory, to measure kinetic and stride characteristics during a trail running time trial, and then analyse the data for correlations with trail running performance. Runners (13 men, 4 women: mean age: 29±5 years; stature: 179.5±0.8 cm; body mass: 69.1±7.4 kg) performed laboratory tests to determine 〖V ̇O〗_2max, running economy, and anthropometric characteristics. On a separate day they performed an outdoor trail running time trial (two 3.5 km laps, total climb: 486 m) while we collected kinetic and time data. Comparing lap 2 with lap 1 (19:40±1:57 min vs. 21:08±2:09 min, P<0.001), runners lost most time on the uphill sections and least on technical downhills (-2.5±9.1 s). Inter-individual performance varied most for the downhills (CV>25%) and least on flat terrain (CV<10%). Overall stride cycle and ground contact time (GCT) were shorter in downhill than uphill sections (0.64±0.03 vs. 0.84±0.09 s; 0.26±0.03 vs. 0.46±0.90 s, both P<0.001). Force impulse was greatest on uphill (248±46 vs. 175±24 Ns, P<0.001) and related to GCT (r=0.904, P<0.001). Peak force was greater during downhill than during uphill running (1106±135 vs. 959±104 N, P<0.01). Performance was related to absolute and relative 〖V ̇O〗_2max (P<0.01), vertical uphill treadmill speed (P<0.001) and fat percent (P<0.01). Running uphill involved the greatest impulse per step due to longer GCT while downhill running generated the highest peak forces. 〖V ̇O〗_2max, vertical running speed and fat percent are important predictors for trail running performance. Performance between runners varied the most on downhills throughout the course, while pacing resembled a reversed J pattern. Future studies should focus on longer competition distances to verify these findings and with application of measures of 3D kinematics.